The Effectiveness of Sociodrama Techniques in Group Guidance Services to Reduce Cyberbullying Behavior - Brilliyent Insani; Diana Septi Purnama (Sakura Digital Nusantara, 2026)
Cyberbullying has become a significant concern among adolescents due to the rapid expansion of digitally mediated communication and limited emotional awareness in online interactions. This study aimed to examine the effectiveness of sociodrama-based group guidance in reducing cyberbullying behavior among students while emphasizing the role of reflective observer participation during intervention activities. The study employed a quantitative quasi-experimental design using a non-equivalent control group design. Participants consisted of 26 tenth-grade students at Madrasah Aliyah Laboratorium Jambi, Indonesia, who demonstrated high levels of cyberbullying behavior and were assigned to experimental and control groups. The experimental group participated in eight sessions of structured sociodrama-based group guidance integrating role-playing, emotional reflection, and observer-based evaluation, whereas the control group received conventional counseling services. Data were collected using a validated cyberbullying behavior scale and analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. The findings revealed a significant reduction in cyberbullying behavior among students who participated in the sociodrama intervention. The experimental group demonstrated a mean score reduction from 62.54 to 37.92, whereas the control group showed only a modest decrease from 62.46 to 56.92. Statistical analysis indicated significant post-intervention differences between groups (p = .001, r = .83), reflecting a large intervention effect. The findings suggest that sociodrama-based group guidance promotes empathy, emotional awareness, perspective-taking, and responsible digital behavior through experiential and reflective learning processes. This study contributes to the development of school counseling interventions by highlighting the importance of reflective observer involvement in cyberbullying prevention programs.